Community empowerment on the improvement of Sofia's cistik home-cooked food product processing in Kalitengah Village, Magelang - Hary Abdul Hakim; Chrisna Bagus Edhita Praja; Suharso Suharso; Fadillah Sandy; Putri Dwi Arianti; Dian Novitasari Anggraeni; Ahmad Agung Febrianto; Rakhmat Dian Hidayat; Panji Nagaro; Diana Setiawati (Universitas Muhammadiyah Magelang, 2023)
The purpose of the implementation of this service program is to increase the production and marketing of processed home-cooked food products, Cistik Sofia, in the Kalitengah Hamlet, Magelang. Most of people in Kalitengah, Glagahombo Village, Tegalrejo District, Magelang Regency are currently starting to develop their businesses in the field of processed snack products in the form of Cheese Sticks. Processed food is used as an alternative business for residents in improving their welfare. This service is carried out through mentoring and training. The results obtained from the implementation of this program, the partners are able to develop variations in product flavors, innovated on the packaging models, and found the new strategies on the marketing process through social media.